Analysis method of feeder partition capacity considering power supply security and distributed generation. Issue 13 (19th January 2018) - Wang, Weifu; Cao, Zhaojing; Sun, Ke; He, De; Sun, Yanjun; Li, Chunxiao; Sun, Ming; Dong, Shufeng
Abstract : Large‐scale integration of distributed generation (DG) increases the stability of the distribution network which in turn makes the network structure more complex to analyse. Thus, this study proposes a feeder partition available capacity calculation model considering N − 1 security verification and DG, in order to provide data support for distribution network's operation and planning. Firstly, the authors discuss DG's different categories and respective treatment in N − 1 fault. Secondly, a calculation method of feeder partition available capacity is proposed for the distribution network with a high permeability of DG. Finally, the calculation results of a practical distribution network prove the practicability and effectiveness of the proposed method.